[tex]48x^3-4x^2+18x-40 \text{ is the product of } (8x^2+6x+8)(6x-5)[/tex]
Solution:
Given that we have to multiply the polynomials
[tex](8x^2+6x+8)(6x-5)[/tex]
Multiplying polynomials is similar to multiplying numbers
When you multiply two terms together you must multiply the coefficient (numbers) and add the exponents
Let us multiply the given polynomials
[tex]\rightarrow (8x^2+6x+8)(6x-5)[/tex]
Multiply each term in first bracket with each term in second bracket
[tex]\rightarrow (8x^2)(6x) -5(8x^2)+6x(6x)+6x(-5)+8(6x)+8(-5)[/tex]
Add the exponents and multiply the coefficients
[tex]\rightarrow 48x^3-40x^2+36x^2-30x+48x-40[/tex]
Combine the like terms -30x and 48x
[tex]\rightarrow 48x^3-40x^2+36x^2+18x-40[/tex]
Combine the like terms [tex]-40x^2 \text{ and } 36x^2[/tex]
[tex]\rightarrow 48x^3-4x^2+18x-40[/tex]
Thus the polynomials has been multiplied